Investigation of triiodothyronine, thyroxine, and thyroid-stimulating hormone levels’ influence on atrial myocardial electrical instability in experimental hypothyroidism - Ruslan F. Rakhmatullov; Renata E. Dementeva; Alina E. Sheina; Kristina P. Kondrateva; Fagim K. Rakhmatullov; Ludmila V. Melnikova (КардиоСоматика)
BACKGROUND: Identifying the association between thyroid dysfunction and the development of nonvalvular atrial fibrillation (AF) remains one of the complex and pressing issue in contemporary cardiology. To date, only a limited number of studies have examined the relationship between AF and the hypothalamic-pituitary-thyroid (HPT) axis, and the available findings are often contradictory. Few papers have explored the association between AF and HPT axis in experimental conditions.